Computational modelling of transport phenomena in high energy materials processing application: large eddy simulation and parallelisation. (1st January 2011) - Chatterjee, Dipankar
A comprehensive three-dimensional numerical model is presented in order to address the coupled turbulent momentum, heat and species transport during molten metal-pool convection in association with continuous evolution of solid-liquid interface typically encountered in high energy materials processing applications. The turbulent aspect is handled by a large eddy simulation (LES) model and the phase changing phenomena is taken care of by a modified enthalpy-porosity technique. The proposed finite volume based LES model is subsequently parallelised for effective computational economy. To demonstrate the effectiveness of the present model, a systematic analysis is subsequently carried out to simulate a typical high power laser surface alloying process, where the effects of turbulent transport can actually be realised.